Analysis quality characteristics of virgin coconut oil (VCO): comparisons with cooking coconut oil (CCO) - Dewi Natalia R; Ayu Natalia; Fendri Lukmanto; Ika Ani; Indra Lasmana Tarigan (Medical Laboratory Analysis and Sciences Journal, 2019)
This study aims to examine the quality of cooking coconut oil (CCO) and virgin coconut oil (VCO). The analysis was carried out as a physical parameter test including organoleptic and density while the chemical parameter test was: free fatty acid (FFA) peroxide number and test of saponification number. The sample oil used comes from coconut oil made traditionally by virgin coconut oil or commonly abbreviated as VCO, which is coconut oil which passes through a different extraction process with ordinary coconut oil so it is believed to have higher quality and provide more benefits. Samples derived from coconut oil traditionally processed in Beji Village, Boyolangu District with the brand "MALIKA". It was found that both oils had relatively the same physical parameters, the difference in density on VCO and CCO: 0.88 g / ml and 0.82 g / ml. As for the chemical parameters of free fatty acids, peroxide numbers, and saponification numbers of the VCO and CCO comparisons: 0.165: 0.207; 0.54: 0.68; 203: 321, so that the overall VCO has good quality, while CCO has an unfavorable saponification number.